Development of sensor using graphical user interface - Saidin, Muhamad Zulfikri (2007)
A sensor is a device that measures or detects a real-world condition, such as motion, heat or light. When flow sensors are devices used for measuring the flow rate or quantity of a moving fluid or gas. The key in selecting correctly between the many available flow sensors and flow meters is one of the requirements of the particular application. The purpose for this project is to interface the flow sensor with MATLAB GUI. The MATLAB GUI will display the result and the data that will get from the flow sensor. To interface between them the PIC 16F877 and MAX232 will be use. The PIC will convert the analog data to digital data and MAX232 will connect the PIC to serial port at computer. This is to make sure the computer (GUI) will be able to read the data. As a result, flow measurement using GUI is able to display generated signal from the developed flow sensor.